P05.09 Detection of clinically relevant mutations in the cerebrospinal fluid of patients with central nervous system metastases. (19th September 2018) - Moya, I; Villatoro, S; Mayo, C; Balada, A; Viteri, S; González-Cao, M; Karachaliou, N; Pons, F; González, X; Rosell, R
Abstract: Background: Mutation analyses in solid tumors are usually performed in tissue biopsies. However, in a significant number of patients, the availability of biopsies is limited, particularly at relapse. Liquid biopsies can be an alternative in this setting. In patients with central nervous system (CNS) metastases, the collection of cerebrospinal fluid (CSF) is challenging but it can be a better material for genetic analyses than blood. In addition, diagnosis of CNS metastases is based on clinical, radiological and cytological data, but CSF is often negative for tumor cells and can lead to a misdiagnosis. Mutational testing in CSF can help to avoid this problem. Material and Methods: Patients with EGFR (n=7) or KRAS-mutant (n=1) lung adenocarcinoma and BRAF-mutant melanoma (n=2) were included in the study. CSF was collected at initial diagnose (n=1) or at progression to systemic therapies (n=9) and paired blood samples were simultaneously drawn in all cases. All 10 patients had CNS metastases at the time of CSF collection, and 3 also presented extra-CNS tumor involvement. CSF was centrifuged, circulating-free DNA was isolated using an automatic extractor (Qiasymphony) and mutation testing was performed by Taqman® in presence of PNAs. Results: EGFR, KRAS or BRAF mutations were identified in the cfDNA isolated from CSF in all the 10 patients included in the study. In the three patients with additional extra-CNS metastases, mutations were also identified in blood, although allelic fractions were lower than in CSF. In contrast, the 7 patients with no extra-CNS involvement were negative in blood. In two EGFR-mutant patients progressing to EGFR TKIs, a T790M mutation was detected exclusively in CSF. Finally, in a KRAS-mutant NSCLC patient repeated CSF samples could be obtained and the evolution of the KRAS mutation related to the clinical outcome. Conclusion: Mutation analysis in CSF is feasible in patients with CNS metastases and provides useful clinical information.